2018
DOI: 10.1038/s41598-018-33403-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent platelet activation and apoptosis in virologically suppressed HIV-infected individuals

Abstract: Cardiovascular diseases and thrombotic events became major clinical problems in the combined antiretroviral therapy (cART) era. Although the precise mechanisms behind these clinical problems have not been fully elucidated, a persistent pro-inflammatory state plays a central role. As platelets play important roles on both, thrombus formation and inflammatory/immune response, we aimed at investigating platelet function in HIV-infected subjects virologically controlled through cART. We evaluate parameters of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 55 publications
6
69
2
Order By: Relevance
“…Furthermore, eRT in platelets also serves as a novel mechanism of translational control through the formation of RNA-DNA hybrids. Our findings also support published studies of platelets in HIV, where PLHWA have, in general, evidence of increased platelet activation, mitochondrial stress, and reactive oxygenation species generation [2,3].…”
supporting
confidence: 91%
“…Furthermore, eRT in platelets also serves as a novel mechanism of translational control through the formation of RNA-DNA hybrids. Our findings also support published studies of platelets in HIV, where PLHWA have, in general, evidence of increased platelet activation, mitochondrial stress, and reactive oxygenation species generation [2,3].…”
supporting
confidence: 91%
“…We and others have previously shown that platelets from dengue infected patients have features of cellular activation 3335,39,47,53 . Platelet activation has been also reported in subjects chronically infected with HIV and there is evidence for persistent platelet activation even when virologic suppression is achieved through ART 38,41 . To assess platelet activation in patients coinfected with DENV and HIV-1 we evaluated the surface expression of the activation marker P-selectin (CD62-P) and the synthesis of nitric oxide (NO) in platelets obtained from dengue infected and HIV plus dengue coinfected patients at the febrile and critical phases of dengue illness compared to samples obtained at the recovery.…”
Section: Resultsmentioning
confidence: 92%
“…We have recently reported that HIV-infected subjects under stable ART have evidence for persistent platelet activation and exhausted platelet α-granules content, even after virological suppression through ART 41 . We therefore hypothesized that exhausted granules in platelets from HIV-infected subjects before coinfection with DENV may affect platelet chemokine secretion during dengue illness resulting in lower levels of platelet-derived chemokines in plasma, as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 65 Indeed, platelet activation persists even in virologically suppressed HIV infection. 169 Viral enzymes such as neuraminidase can cause desialylation of platelet surface receptors, 6 and desialylation might promote platelet clearance in the liver. 170 171 …”
Section: Platelet Interactions With Virusesmentioning
confidence: 99%